ANALISIS PENGARUH USAHA MIKRO, KECIL, DAN MENENGAH DALAM PEMBERDAYAAN MASYARAKAT UNTUK MENGURANGI KEMISKINAN DI KABUPATEN TANGERANG - Puspita, Christin Clara; Uguy, Leroy Samy (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The uneven distribution of economic growth throughout Indonesia is evidenced by the high income gap between regions. Poverty is currently the main problem in the context of poverty alleviation in Indonesia. The current situation shows that the root cause of poverty is still a complex and growing challenge. To fight poverty, this requires joint efforts from various power holders, including governments and civil society, non-governmental organizations (NGOs), and the private sector. Entrepreneurship through MSMEs, especially in Tangerang Regency, has an important role in reducing poverty rates and expanding employment opportunities. The aim of this research is to determine the influence of MSMEs in reducing poverty through community empowerment in Tangerang Regency as well as supporting and inhibiting factors. This research uses a combined quantitative and qualitative approach with data processing using SmartPLS. The sample for this research consisted of 100 people from the MSME population in Tangerang Regency. The data obtained will be integrated to understand the relationship between internal and external factors and efforts to eradicate poverty through community empowerment. The research results show that internal factors of MSMEs have a significant influence on community empowerment in reducing poverty,  internal factors of MSMEs have an influence on community empowerment in Tangerang Regency. External factors of MSMEs have a significant influence on community empowerment in reducing poverty, external factors of MSMEs have an influence on community empowerment in Tangerang Regency. Community empowerment has a significant effect on poverty reduction, community empowerment has an influence on poverty reduction in Tangerang Regency.